Low‐oxygen hormetic conditioning improves field performance of sterile insects by inducing beneficial plasticity. (4th November 2020) - López‐Martínez, Giancarlo; Carpenter, James E.; Hight, Stephen D.; Hahn, Daniel A.
Abstract: As part of sterile insect technique (SIT) programs, irradiation can effectively induce sterility in insects by damaging germline genomic DNA. However, irradiation also induces other off‐target side effects that reduce the quality and performance of sterilized males, including the formation of damaging free radicals that can reduce sterile male performance. Thus, treatments that reduce off‐target effects of irradiation on male performance while maintaining sterility can improve the feasibility and economy of SIT programs. We previously found that inducing a form of rapid, beneficial plasticity with a 1‐hr anoxic‐conditioning period (physiological conditioning hormesis) prior to and during irradiation improves male field performance in the laboratory while maintaining sterility in males of the cactus moth, Cactoblastis cactorum . Here, we extend this work by testing the extent to which this beneficial plasticity may improve male field performance and longevity in the field. Based on capture rates after a series of mark release–recapture experiments, we found that anoxia‐conditioned irradiated moths were active in the field longer than their irradiated counterparts. In addition, anoxia‐conditioned moths were captured in traps that were farther away from the release site than unconditioned moths, suggesting greater dispersal. These data confirmed that beneficial plasticity induced by anoxia hormesis prior to irradiation led to lower postirradiation damage and increased flight performance and recapture duration under field conditions. We recommend greater consideration of beneficial plasticity responses in biological control programs and specifically the implementation of anoxia‐conditioning treatments applied prior to irradiation in area‐wide integrated pest management programs that use SIT.